POTENSI RETRIBUSI DAERAH BAGI PENINGKATAN PENDAPATAN ASLI DAERAH SEBUAH STUDI DI KABUPATEN REMBANG - Mohammad Kanzunnudin (STIE Pelita Nusantara Semarang, 2006)
Potential is the chance or the ability possessing. In this term, the tax contribution from kinds of taxes, one of them is parking retribution to increase the Local gain. Retribution is a citizen’s dues given to state with direct services given as the compensation. Local Gain (Pendapatan Asli Daerah) is a local acceptance of revenue obtained from its own sources, as this has been arranged in locallaws under the state’s regulation. Retribution gained from parking area in Rembang Regency is one of the Local gain, which is maintained by the Local gain Department (Dipenda) of Rembang Regency. This Local Gain can be significantly potential when its maintenance is held in both intensification and extentification.